PUPUK ORGANIK CAIR DARI AIR LIMBAH LELE SISTEM BIOFLOK HASIL FERMENTASI AEROB DAN AN AEROB - Dedi Pardiansyah; Nasir Ahmad; Firman Firman; Suharun Martudi (University of Prof. Dr. Hazairin, SH, 2019)
The biofloc system catfish wastewater is in the form of accumulation of organic residues from feed residues, catfish manure, feed particles and bacteria and algae, because the biofloc catfish cultivation wastewater can be processed into organic fertilizer especially liquid organic fertilizer. The study used a completely randomized single factor treatment with an aerobic (A) fermentation process and Anaerobic fermentation process (B). Each treatment was repeated 8 times to obtain 16 experimental units. Furthermore, the results of the study data were analyzed by variance at the level of 5 percent. The results showed that the growth rate of catfish was very good. Where growth continues to increase the 10th day observation until the end of the study. While the content of N, P and K in the POC produced did not show a significant difference between POC fermented by Aerob and Anaerob. POC content fermented by Aerob; N = 1.645, P = 0.326 and K = 1.143 while Anaerobic fermentation; N = 2.189, P = 0.278 and K = 1.165.